An investigation of photovoltaic devices based on p‐type Cu2O and n‐type γ‐WO3 junction through an electrolyte solution containing a redox pair. (13th September 2020) - Resende, Andressa L. S.; Costa, Antonio G. R.; Lima, Aline E. B.; Costa, Maria J. S.; Longo, Elson; Cavalcante, Laécio S.; Santos, Reginaldo S.
Summary: In this article, we report a solar cell prepared with p ‐type cuprous oxide (Cu2 O) and n ‐type gamma‐tungsten oxide (γ‐WO3 ) films combined by an redox electrolyte in a configuration similar to that used in dye‐sensitized solar cells. Cu2 O films were prepared by the electrochemical method in three different pH conditions. X‐ray diffraction patterns revealed that the Cu2 O films presented a crystalline phase with cubic structure after deposition, whereas the n ‐type γ‐WO3 film was prepared by the drop‐casting method. Optical analyses showed that both oxide films absorb visible light. After the photoelectrochemical characterization of the films, solar cells configured like a "sandwich" (Cu2 O/electrolyte/γ‐WO3 ) were assembled and investigated under irradiation of 100 mW cm −2 . The solar cell with I − / I 3 − redox pair showed better results than that prepared with polysulfide K2 S/ S n 2 − electrolyte. For each solar cell, the investigated parameters were short‐circuit current density, open‐circuit voltage, fill factor, maximum power, and cell efficiency. The method proposed here can be considered new, promising, and simple for the preparation of solar cells with a p – n junction. Abstract : Here, we present a new study with a solar cell prepared with a configuration based on Cu2 O and γ‐WO3 films p – n junction through an electrolyte solution containing a redox pair. The best electrochemical Cu2 O film synthesis conditions were reached in pH 11. The solar cell prepared with the pair I – /I3 – provided the best results. This modern proposal for a solar cell is a very simple, fast, low cost, and with potential applications in photovoltaic devices.